Teknologi Dalam Rekrutmen: Pengaruh Kebijakan Skor Kredit Terhadap Rekrutmen Karyawan Berbasis Web - Rohmatul Putri Choiroh; Nila Fitriana; Jaka Arif Rahman Hidayat; Chinta Aulia Puja Lista Kumala; Mochammad Isa Anshori (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
Purpose - In this era, technological advances cannot be separated from human life, one of which is the employee recruitment process carried out by companies. The purpose of writing this article is to examine the influence of technology on the employee recruitment process. With advances in technology, the recruitment process can be carried out more effectively and efficiently. Design/methodology/approach-By using data analysis methods from various journals, books, articles and literature, the recruitment process is carried out quite in length, starting from distributing job vacancies, collecting files, selecting and making decisions to hire employees who suit the company's needs, especially now that there is a credit score policy. Of course, if done manually it will take a long time, and archiving data cannot be done efficiently. For this reason, technological advances must be utilized optimally to facilitate the employee recruitment process. Findings-The findings from the literature that have been reviewed are that technology has a positive and quite large influence on the employee recruitment process. and the existence of a credit score policy in the employee recruitment process. Practical implications - With a credit score policy and using the web to manage the employee recruitment process, the company will easily recruit employees and manage prospective employee data and analyze credit score data so that the company can easily obtain quality human resources according to the company's needs.